2012
DOI: 10.1007/s11065-012-9192-3
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Sequelae of Blast-Induced Traumatic Brain Injury: Recovery and Rehabilitation

Abstract: Blast-related traumatic brain injury (bTBI) poses a significant concern for military personnel engaged in Operation Enduring Freedom and Operation Iraqi Freedom (OEF/OIF). Given the highly stressful context in which such injury occurs, psychiatric comorbidities are common. This paper provides an overview of mild bTBI and discusses the cognitive sequelae and course of recovery typical of mild TBI (mTBI). Complicating factors that arise in the context of co-morbid posttraumatic stress disorder (PTSD) are conside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
65
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(69 citation statements)
references
References 167 publications
3
65
0
Order By: Relevance
“…This is consistent with some previous findings, which favored multidisciplinary practices in RTW interventions [11,64,65]. Watanabe [66] found that greater gains in cognitive functions can be achieved through a multidisciplinary approach to rehabilitation.…”
Section: Discussionsupporting
confidence: 92%
“…This is consistent with some previous findings, which favored multidisciplinary practices in RTW interventions [11,64,65]. Watanabe [66] found that greater gains in cognitive functions can be achieved through a multidisciplinary approach to rehabilitation.…”
Section: Discussionsupporting
confidence: 92%
“…Multiple deployments and increased use of improvised explosive devices (IED) in Iraq and Afghanistan have resulted in higher rates of exposures to blasts, and have possibly contributed to elevated rates of mTBI and stress-related health problems such as PTSD [26,136]. Substantially different mTBI prevalence rates have been reported for the US, UK, and Canada [26,152,193].…”
Section: Discussionmentioning
confidence: 99%
“…Substantially different mTBI prevalence rates have been reported for the US, UK, and Canada [26,152,193]. This may be due to differing research methodology, the different types of risks/exposures faced by the sample, or differing lengths of deployment [153].…”
Section: Discussionmentioning
confidence: 99%
“…[12][13][14] Closedhead blast injury is the signature injury, 12 and the cognitive sequelae, recovery, and rehabilitation are of increasing concern. 15 It is estimated that there are as many as 320,000 veterans who have returned with TBI, most with mTBI. 16,17 Post-traumatic stress disorder (PTSD) is also a major concern with OEF/OIF soldiers who have experienced mTBI.…”
mentioning
confidence: 99%